2022
DOI: 10.1155/2022/1344946
|View full text |Cite
|
Sign up to set email alerts
|

Melissa officinalis L. Supplementation Provides Cardioprotection in a Rat Model of Experimental Autoimmune Myocarditis

Abstract: Due to existing evidence regarding antioxidant and anti-inflammatory effects of Melissa officinalis extracts (MOEs), this study was aimed at investigating the potential of ethanolic MOE to prevent the development of myocarditis and its ability to ameliorate the severity of experimental autoimmune myocarditis (EAM) by investigating MOE effects on in vivo cardiac function, structure, morphology, and oxidative stress parameters. A total of 50 7-week-old male Dark Agouti rats were enrolled in the study and randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…However, insufficient evidence is available regarding the ME effects on cardiac morphology, except for the decrement in the infarct size after a 5-day reperfusion period, found in a study by Sedighi et al [26]. Additionally, we found that 7-day preconditioning with ME200 achieved to prevent myocardial fibrosis induced by I/R injury, which is in line with our previous research in a different model of heart disease, autoimmune myocarditis [28]. This can partly be explained by the fact that rosmarinic acid exerts antifibrotic action in the heart via AMPKα/Smad3 signaling pathway, proved both in vivo and in vitro [34].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, insufficient evidence is available regarding the ME effects on cardiac morphology, except for the decrement in the infarct size after a 5-day reperfusion period, found in a study by Sedighi et al [26]. Additionally, we found that 7-day preconditioning with ME200 achieved to prevent myocardial fibrosis induced by I/R injury, which is in line with our previous research in a different model of heart disease, autoimmune myocarditis [28]. This can partly be explained by the fact that rosmarinic acid exerts antifibrotic action in the heart via AMPKα/Smad3 signaling pathway, proved both in vivo and in vitro [34].…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, other research provided evidence that HR decrement can be induced by a low dose of lemon balm extract (ME50) after the reperfusion period [ 26 ]. This can be explained by the fact that lemon balm may act negatively chronotropic in different ways: by blockage of K + channels or by cardiac muscarinic receptors activation [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This EAM model is histologically similar to acute human myocarditis, with macrophage, lymphocyte, and neutrophil recruitment accompanying cardiac fibrosis [ 4 ]. Given that the present therapy choices for myocarditis are confined to symptoms as arrhythmias and heart failure, and that no other strategy has yet been discovered [ 5 ], innovative effectual therapeutic alternative is indispensable. Natural products are becoming more popular in the treatment of cardiovascular disease due to their security, less side effects, and reduced prices.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are becoming more popular in the treatment of cardiovascular disease due to their security, less side effects, and reduced prices. In current years, preclinical and clinical research has concentrated on discovery novel phyto-medicines, such as plant extracts with significant anti-inflammatory and antioxidant action, and, in particular, active constituents for cardioprotection [ 5 ]. Some plants, such as the Indian plant Boswellia serrata (B. serrata ), have antioxidant qualities that are useful in the treatment and prevention of various ailments.…”
Section: Introductionmentioning
confidence: 99%